2001
DOI: 10.1093/genetics/159.3.1151
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for New Alleles in the Protein Kinase Adenosine Monophosphate-Activated γ3-Subunit Gene Associated With Low Glycogen Content in Pig Skeletal Muscle and Improved Meat Quality

Abstract: Several quantitative trait loci (QTL) affecting muscle glycogen content and related traits were mapped to pig chromosome 15 using a three-generation intercross between Berkshire × Yorkshire pigs. On the basis of the QTL location the PRKAG3 (protein kinase, AMP-activated, γ3-subunit) gene was considered to be a good candidate for the observed effects. Differences in the PRKAG3 gene sequences of the founder animals of the intercross were analyzed. The RN− mutation previously reported was not present in the cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 206 publications
(38 citation statements)
references
References 27 publications
2
36
0
Order By: Relevance
“…On the other hand, the protein encoded by the PRKAG3 gene is a regulatory subunit of the AMP activated protein kinase (AMPK), which plays a key role in the regulation of glucose and energy metabolism in skeletal muscle. Glycogen content is determinant of multiple meat quality traits, such as pH, meat color, drip loss or tenderness(Ciobanu et al, 2001). The ampli ed PCR product for PRKAG3 or RN (199I>V and 200R>Q) SNP was 114 bp in length, which was similar to the ndings ofJosell et al (2003) andLindahl et al (2004).…”
supporting
confidence: 52%
See 4 more Smart Citations
“…On the other hand, the protein encoded by the PRKAG3 gene is a regulatory subunit of the AMP activated protein kinase (AMPK), which plays a key role in the regulation of glucose and energy metabolism in skeletal muscle. Glycogen content is determinant of multiple meat quality traits, such as pH, meat color, drip loss or tenderness(Ciobanu et al, 2001). The ampli ed PCR product for PRKAG3 or RN (199I>V and 200R>Q) SNP was 114 bp in length, which was similar to the ndings ofJosell et al (2003) andLindahl et al (2004).…”
supporting
confidence: 52%
“…Pairwise linkage disequilibrium between SNPs was used to measure the linkage disequilibrium (LD). This study provides an overview of LD patterns between SNPs related to meat quality in different subpopulations of Creole (11) and commercial pigs (13). It is observed that not all pairs of SNPs present statistically signi cant associations.…”
Section: Genetic Diversity Parameters and Population Genetic Structurementioning
confidence: 95%
See 3 more Smart Citations